Artista-professor: cartografia e processo - Paste, Rosana Lucia (2017)
It is about investigating the contaminations, assemblies, ordinary plans of the artist who is a teacher, describing the existence of lines joining these professions, how they relate and complement each other. We chose to chart experiences that reveal the creating process of those researched. The cartographic practice is averse to unifications and promotes its openness to variations, multiplicities, deviations and indeterminations. Access to production enabled us to follow the creative paths with their tracks and clues in the form of sketches, notes, daydreams, with the perspective of approaching what is unique in the process of creation of each artist-teacher. We use philosophical principles of territoriality, rhizome, heterogenesis connection and multiplicity of Giles Deleuze and Felix Guattari. The choice for philosophy in research is to allow the facts to be analyzed in their own, being immanences that arise and overlap, differently from history, which limits and conditions them to a single truth. The artists-teachers researched were Lygia Clarck, Rosana Paste and José Carlos Vilar.